Quid pro quo as a form of sexual harassment in the South African employment law :a critical review - Hobyani, Tivani Musa (My University, 2024)
This study examines the effects of the conduct of quid pro quo in the workplace by analysing the law applicable, its elements (consent in particular), as well as the extent to which the conduct constitute corruption. Quid pro quo is a latin concept which means “something for something”. For the purposes of this study, the concept of quid pro quo is discussed in context of sexual harassment. It is not unusual that individuals who are in position of power in the workplace demand sexual gratification in exchange for employment favour. This has a long-standing effect on the relationship of the victim and the harasser. The Code of Good Practice on Sexual Harassment recognises quid pro quo as one of the forms of sexual harassment. Despite being legally recognised, quid pro quo is the most ignored form of sexual harassment. While workplace quid pro quo harassment is well known, the public ordinarily consider it as an immoral activity rather than as sexual harassment. In circumstances where quid pro quo involves sexual penetration, a question of whether it qualifies as rape, or a separate form of sexual offence rises for consideration. The study found that the consent given in quid pro quo, especially one resulting from a threat, is invalid and therefore quid pro quo conduct which include sexual penetration is an equivalent of criminal law crime of rape. The validity of consent has been evaluated in consideration of factors influencing consent, including but not limited to the need for employment and power relations. Further, the study also shows that quid pro quo constitutes the crime of corruption, in line with the Prevention and Combating of Corrupt Activities Act 12 of 2004. The study evaluates the legal framework, including the approach adopted by the legislature and the courts in responding to the effect of quid pro quo harassment in the South African employment law.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2024
Keywords: Sexual harassment; Quid pro quo harassment; Rape; Employees; Employment; Consent; Corruption; Sexual harassment; Consent (Law); Sexual harassment -- Law and legislation